Wielość wartości dostrzeganych w filmach przyrodniczych przez studentów = Multitude of values noticed by students in natural scientific films - Wiatrowska, Leokadia (Zielona Góra: Lubuskie Towarzystwo Naukowe)
Mass media, as a generally available means of transfer, have the possibility to influence human personality, because of their diverse program themes. Natural scientific films are nowadays really popular to watch. Animal lifestyles are shown in them in a natural way. It is interesting, surprising, intriguing, and shocking. They generate a whole spectrum of values, attitudes or behavior types, which not always have a positive effect on the human psyche. They also evoke emotions which are dysfunctional, like fear, sadness, hatred, or anger. In present days also another type of influence caused by these films has emerged, and that is therapy.
Keywords: film przyrodniczy; studenci; wartości